Genetic diversity analysis in cashew (Anacardium occidentale L.) germplasm using RAPD marker: Genetic distance in germplasm using RAPD - Bhadra, T; Obaidullah, AZM; Sultana, Mst Sabiha; Ahmed, M; Islam, MM (Journal of the Bangladesh Agricultural University, 2019)
Anacardium occidentale L., commonly known as cashew nut, belongs to the family Anacardiaceae. It is regarded as a high valued fruit nut crop world-wide. Potential of this economically important nut is under-utilized in Bangladesh in spite of having all favorable agro-climatic conditions. The objective of the present investigation was to characterize six cashew accessions using Random Amplified Polymorphic DNA (RAPD) markers. Four random primers viz. OPE-02, OPE-18, OPK-03 and OPB-15 were used to amplify DNA segments. A total of 33 reproducible bands were obtained, out of which 11 were monomorphic and 22 were polymorphic. On average 74.12% polymorphism was observed. . Primers OPB-15 and OPK-03 yielded 100% polymorphism and OPE 02 and OPE 18 produced 33.33% and 63.16 % polymorphism, respectively. Cluster analysis revealed two main distinct groups, first group included GP-1 and the second consisted of five genotypes viz. GP-2, GP-3, GP-4, GP-5and GP-6 The major cluster- II was further subdivided into two minor clusters i.e. minor cluster- III and IV. Minor cluster- III contained only one genotype GP-4. Minor cluster- IV consists of four rest genotypes. The genetic distance between the groups was found low and varied from 0.002 to 0.0308. Maximum genetic distance was observed between GP-1 and GP-2cashew germplasm and minimum between GP-5 and GP-6. The low genetic distance which is unusual for this out crossing long-lived tree species, indicates the probability of having common ancestry among the germplasm or may be due to the use of a narrow range of populations for the investigation. <!--StartFragment --> J Bangladesh Agril Univ 17(4): 461–465, 2019